Size Controlled Synthesis of FeCo Alloy Nanoparticles and Study of the Particle Size and Distribution Effects on Magnetic Properties - A. Shokuhfar; S. S. S. Afghahi (Advances in Materials Science and Engineering)
In this research the size controlled synthesis of FeCo nanoparticles was done using a quaternary microemulsion system. X-ray diffraction and high resolution transmission electron microscopy of as-synthesized nanoparticles confirm the formation of FeCo alloy nanoparticles. The effects of two process parameters, namely, water to surfactant molar ratio and molar concentration of metal salts, on the size and size distribution of nanoparticles were discussed by the aid of transmission electron microscopy. The size dependency of magnetic properties was also investigated using a room temperature vibrating sample magnetometer. The superparamagnetic-ferromagnetic and single domain-multidomain transition sizes were determined. Then the specific absorption rates at transition sizes were calculated and the best sample for magnetic hyperthermia treatment was introduced.